Mutational analysis of BRCA1 and BRCA2 genes in women with familial breast cancer from different regions of Colombia. (2019)
The main risk factor for familial breast cancer is the presence of mutations in BRCA1 and BRCA2 genes. The prevalence of mutations in these genes is heterogeneous and varies according to geographical origin of studied families. In Colombia mutations in these genes have been mainly studied on patients from Andean region. Bogot and Medellin presented its own battery of mutations. This study aims to identify mutations in BRCA1-2 genes in women with familial breast cancer from different regions of Colombia.